The Effects of Problem-Based Learning on Science Learning Achievement and Scientific Mind in the Topic of the Movement of the Sun for Grade 3 Students - Suvapong, Suvapan (An Online Journal of Education, 2026)
This research aimed to: 1) compare learning achievement in science subject on the topic of the movement of the sun before and after using problem-based learning (PBL) among grade 3 students; 2) compare the post-learning achievement against the 75 percent criterion; and 3) investigate the students’ scientific mind after after learning. The sample group consisted of 105 grade 3 students from a school in Yasothon province, enrolled in the first semester of the 2022 academic year, obtained via cluster random sampling. The research instruments included: 1) a problem-based learning lesson plan with IOC values ​​between 0.80-1.00 2) a learning achievement test with a reliability of 0.84 and 3) a psychological student self-assessment measuring scientific mind with a reliability of 0.87. Statistics used in the study included percentage, mean (M), standard deviation (SD) and a dependent t-test. The results of the study revealed that: 1) the students’ post-learning achievement scores were significantly higher than their pre-learning scores at the .05 level; 2) the post-learning mean score was significantly higher than the 75 percent criterion at the .05 level; and 3) the students’ overall scientific mind was at the highest level (M = 4.58, SD = 0.67). When considering specific aspects, carefulness received the highest mean score (M = 4.77, SD = 0.91), followed by rationality (M = 4.69, SD = 0.42) and honesty (M = 4.68, SD = 0.41) respectively. All three aspects were at the highest level.